Effect of psychological empowerment on human resource management with the mediating role of emotional engagement in employees of selected sport federations - Khodadad Kashi, Sholeh; Saatchian, Vahid (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this research was to investigate the effect of psychological empowerment on human resource retention in selected sports federations, with the role of emotional commitment as a mediating factor. A cross-sectional study was carried out. The statistical population of the study (270 employees) was all official staff of five selected federations (wrestling, volleyball, taekwondo, soccer and swimming). Based on the Morgan table, 175 individuals were selected as the statistical sample. In order to assess the studied variables, Spritzer’s psychological empowerment questionnaire (1995), Allen and Meyer Commitment Measurement Questionnaire (1991), and Kaident’s staff retention questionnaire (2009) were used. The reliability of the questionnaires was 0.89, 0.87, and 0.84, respectively. In order to analyze the data, descriptive and inferential statistics (Kolmogorov Smirnov, Pearson Correlation Coefficient, Path Analysis Model) were used. The results showed that there is a statistically significant positive correlation between psychological empowerment and human resources maintenance (0.56). Emotional commitment with an impact factor of 0.35 plays a mediating role in relation to psychological empowerment in human resource retention. Therefore, the officials of sports federations can improve the maintenance of human resources by establishing a complete and desirable psychological empowerment and paying attention to the concept of emotional intelligence at the organization level.